Analisis Ketersediaan Bahan Baku Dan Prospek Pengembangan Usaha Penyulingan Minyak Atsiri Daun Cengkeh Di Kecamatan Watulimo Kabupaten Trenggalek - Firmantya Mukti Bahari; Rudi Wibowo (UPT Penerbitan Universitas Jember, 2018)
Watulimo district is one of districts in Trenggalek that produces cloves. The potency of this plant at Watulimo district Trenggalek makes some people build business or agro-industry such as industry of essential oil from clove leaves by utilizing the waste from clove plant. The condition of clove raw material is very influential on essential oil refining business stability and sustainability at Watulimo district. Raw material availability of clove essential oil refining industry must be fulfilled by using raw material inventory control method that is appropriate and it can minimize the cost, so that the industry can continue to run and develop. The research purpose are to know (1) clove leaves as raw material availability level of clove leaves essential oil refining at Watulimo sub district Trenggalek regency, (2) the prospect of clove leaves essential oil refining development at Watulimo district, Trenggalek. The determination of research area was conducted by using purposive methods. The Method of this research uses descriptive and analytic methods. The sample used is one small industry and one home industry. In this research, the researcher used primary and secondary data. The Analysis that used are (1) Material Requirement Planning (MRP) method with Lot For Lot Technique, Economic Order Quantity, Period Order Quantity, and Balancing Part Period, (2) SWOT Analysis. Result of this research, it can be concluded that: (1) the control and the procurement method of raw material of clove leaves essential oil refining industries at Watulimo district is not efficient and economic. MRP method PPB technique is recommended as alternative method in raw material control and procurement in small industry owned by Bapak Sutoyo by saving total cost of Rp. 32.171.717 or 17,22%, whereas MRP method POQ technique is recommended in domestic industry owned by Ibu Nur Utami by saving total cost of Rp. 19.429.800 or 23,11%, (2) SWOT accounting and analysis result showed that clove leaves essential oil refining industries at Watulimo district still in white area position, so it is profitable and has prospective opportunity and potential to do.